Homoeoprophylaxis—A Summary of Latest Developments - Golden, Isaac (Homœopathic Links, 2020)
This article (1) reports on a conference in Delhi in January 2020 directed toward building the evidence base of homoeoprophylaxis, (2) summarizes the latest evidence base supporting the effectiveness of homoeoprophylaxis and (3) advises readers of a change in long-term endemic homoeoprophylaxis programme.
Keywords: homoeoprophylaxis; effectiveness; evidence; programme